2018
DOI: 10.1111/eip.12544
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive nutrients in first‐episode psychosis: A systematic review of efficacy, tolerability and neurobiological mechanisms

Abstract: AimThe effects of nutrient‐based treatments, including adjunctive vitamin or antioxidant supplementation, have been explored extensively in long‐term schizophrenia. However, no systematic evaluation of trials in “first‐episode psychosis” (FEP) has been conducted, despite the potential benefits of using these treatments during the early stages of illness. Therefore, we aimed to review all studies examining efficacy, tolerability and the biological mechanisms of action, of nutrient supplementation in FEP.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…However, the negligible effect sizes after controlling for publication bias, along with the low review quality identified by AMSTAR‐2, reduces confidence in findings. Additionally, whereas the existing meta‐analytic data have found a lack of significant benefits in people with schizophrenia, subsequent trials in young people with first‐episode psychosis have reported more positive, though mixed, results, putatively ascribed to neuroprotective effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, the negligible effect sizes after controlling for publication bias, along with the low review quality identified by AMSTAR‐2, reduces confidence in findings. Additionally, whereas the existing meta‐analytic data have found a lack of significant benefits in people with schizophrenia, subsequent trials in young people with first‐episode psychosis have reported more positive, though mixed, results, putatively ascribed to neuroprotective effects.…”
Section: Discussionmentioning
confidence: 99%
“…These include specific dietitian-led interventions for weight management, which have been shown to be effective in severe mental illness (37). Further exploration is also needed for the use of adjunctive nutrients in people experiencing FEP as a potential method of improving symptoms and functioning (39).…”
Section: Discussionmentioning
confidence: 99%
“…There are preliminary data from RCTs suggesting that anti-inflammatory nutrients, such as omega-3 and folate-based compounds, may also be effective for other SMIs, including bipolar disorder and schizophrenia [43]. Because inflammation is particularly elevated during onset of psychotic disorders, these adjunctive treatments may have neuroprotective effects in the early stages of illness among young people [44] [45] potentially improving cognitive outcomes for some patients. However, the extent to which their effects are due specifically to their antiinflammatory properties is not fully ascertained [46].…”
Section: Introductionmentioning
confidence: 99%